The LifeStories project: Empowering voices and avoiding harm—Ethics protocol of a long-term follow-up study of individuals placed in infant care institutions in Switzerland - Lannen, Patricia; Bombach, Clara; Sticca, Fabio; Simoni, Heidi; Jenni, Oskar G. (Frontiers in Psychology, 2022)
Little empirical data exist to guide ethical decisions when conducting research with vulnerable populations. The current study assesses a protocol designed to mitigate risks in a population-based cohort of 246 individuals placed in care institutions as infants in a non-selective 60-year follow-up. In total, 116 (47%) individuals chose to participate, of whom 53 (55%) reported positive effects of participation such as the opportunity to fill some gaps in their life stories, to better deal with their past, and to understand previous family dynamics. Only three individuals (2.5%) explicitly reported negative short-term consequences such as feeling upset as a result of thinking about stressful times, but they nonetheless rated the usefulness of the study as high. For six participants (5%), psychological counseling sessions were initiated as a support measure. Our findings suggest that risk of harm can be managed with a rigorous ethics protocol when conducting research with a vulnerable cohort and therefore enable the voices of survivors to be heard. A step wise approach in which increasing amounts of information were presented at each step, clearly operationalized passive decline, and direct and consistent contact with highly trained staff were considered key to mitigating distress.